1983
DOI: 10.2190/hjdk-607c-5mwt-h5vc
|View full text |Cite
|
Sign up to set email alerts
|

Wayfinding and Orientation by the Visually Impaired

Abstract: Getting lost can be very stressful. Not only does it entail "real world" consequences of being late for an appointment or missing an airplane flight, it may often cause feelings of panic and discomfort and create serious psychological stress (see Zimring [1] for a review), and in fact several studies suggest that spatial disorientation may be partly responsible for increased deaths by older people immediately after they have been relocated [2]. Whereas spatial disorientation is serious for able-bodied, sighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Orientation is supported by frames of reference, ranging in complexity from landmarks (distinctive man-made or natural features) to route sequences to mental images or cognitive maps. 25,26 Second, wayfinding requires decision making both in advance travel planning, however casual (ie, route choice), and in en route decision-making (ie, behavior at decision points). Field-based researchers using subject think-aloud protocols during wayfinding characterized decision making as situated in the environment; travelers have a general idea of where to go and then work out the details on the move, in response to cues in the environment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Orientation is supported by frames of reference, ranging in complexity from landmarks (distinctive man-made or natural features) to route sequences to mental images or cognitive maps. 25,26 Second, wayfinding requires decision making both in advance travel planning, however casual (ie, route choice), and in en route decision-making (ie, behavior at decision points). Field-based researchers using subject think-aloud protocols during wayfinding characterized decision making as situated in the environment; travelers have a general idea of where to go and then work out the details on the move, in response to cues in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…25,6268 Wayfinding can be further impeded by transient environmental conditions that compromise information gathering such as poor visibility, bad weather, construction, darkness, or sensory overload or even by stressful frames of mind. 26,6972 In addition, several studies suggested spatial anxiety as a barrier to wayfinding that affects individual performance. 40,51,65,73 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nesse caso, a desorientação pode ser muito mais séria e perigosa para esses indivíduos quando não conseguem basear suas estratégias de deslocamento em marcos referenciais ou visualizar obstáculos no caminho (ZIMRING;TEMPLER, 1983).…”
Section: Wayfinding E a Pessoa Com Deficiência Visualunclassified